1999
DOI: 10.1002/(sici)1097-0215(19990531)81:5<779::aid-ijc19>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine enhances penetration and anti-cancer activity of local cisplatin on rat sub-cutaneous and peritoneal tumors

Abstract: Despite the theoretical advantages of a high local concentration of anti‐cancer drugs, local chemotherapy often fails to produce complete and lasting responses in experimental and human solid tumors. Experiments using Patent Blue dye showed that fluids diffused poorly into tumor mass when injected inside or around s.c. rat tumors in rats. In the same way, Patent Blue dye distributed poorly from the peritoneal cavity into the tumor nodules of rats with peritoneal carcinomatosis. The potent vasoconstrictor, epin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…It has been described that administration of anticancer agents immediately after tumor cell inoculation can eliminate all disease, whereas late administration (later than 3 days after tumor inoculation, when usually macroscopic disease is present) may slow down tumor growth but cannot be used with curative intent. [16][17][18][19][20] The current study shows, in accordance with the experimental literature mentioned, that the application of intraperitoneal chemotherapy 1 day after surgery is still effective to eliminate microscopic tumor cells after cytoreductive procedures, without use of hyperthermic circumstances. Twelve animals from the EPIC group and five animals from the HIPEC group were alive at the end of the follow-up period of 24 weeks.…”
Section: Discussionsupporting
confidence: 88%
“…It has been described that administration of anticancer agents immediately after tumor cell inoculation can eliminate all disease, whereas late administration (later than 3 days after tumor inoculation, when usually macroscopic disease is present) may slow down tumor growth but cannot be used with curative intent. [16][17][18][19][20] The current study shows, in accordance with the experimental literature mentioned, that the application of intraperitoneal chemotherapy 1 day after surgery is still effective to eliminate microscopic tumor cells after cytoreductive procedures, without use of hyperthermic circumstances. Twelve animals from the EPIC group and five animals from the HIPEC group were alive at the end of the follow-up period of 24 weeks.…”
Section: Discussionsupporting
confidence: 88%
“…However, the high concentrations of glucose in dialysate solutions led to severe hyperglycemia, and it has been concluded that this adjunct therapy is not viable for clinical use. Duvillard et al (1999) investigated the effect of epinephrine on the penetration of cisplatin and patent blue dye into abdominal tumors after intraperitoneal dosing. They observed that epinephrine strongly enhanced the penetration of the dye into tumor nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Epinephrine is a local vasoconstrictor commonly added to local anesthetic drugs and has recently been used in association with intratumoral and intraperitoneal chemotherapy for enhancement of tumor penetration and antitumoral activity. 39,40 In our experiments, epinephrine greatly enhanced intratumoral transfection rate without any toxicity at the concentration used (1 mg/l).…”
Section: Discussionmentioning
confidence: 58%